2014
DOI: 10.1021/ac403796n
|View full text |Cite
|
Sign up to set email alerts
|

193 nm Ultraviolet Photodissociation Mass Spectrometry for the Structural Elucidation of Lipid A Compounds in Complex Mixtures

Abstract: Here we implement ultraviolet photodissociation (UVPD) in an online liquid chromatographic tandem mass spectrometry (MS/MS) strategy to support analysis of complex mixtures of lipid A combinatorially modified during development of vaccine adjuvants. UVPD mass spectrometry at 193 nm was utilized to characterize the structures and fragment ion types of lipid A from Escherichia coli, Vibrio cholerae, and Pseudomonas aeruginosa using an Orbitrap mass spectrometer. The fragment ions generated by UVPD were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 63 publications
2
77
0
Order By: Relevance
“…Ultraviolet photodissociation (UVPD) is another promising approach for lipid characterization [32,33]. UVPD has recently been implemented on commercial instrumentation, initially requiring significant non-trivial instrument modifications [34,35].…”
Section: +mentioning
confidence: 99%
“…Ultraviolet photodissociation (UVPD) is another promising approach for lipid characterization [32,33]. UVPD has recently been implemented on commercial instrumentation, initially requiring significant non-trivial instrument modifications [34,35].…”
Section: +mentioning
confidence: 99%
“…As a promising alternative, UVPD is a higher energy activation method that has demonstrated advantages over CID for characterization of a wide range of biopolymers (including lipids, proteins, peptides, nucleic acids, and glycans). 41,4366 Hybrid activation methods consisting of UVPD in conjunction with CID or electron transfer dissociation (ETD) have also been developed as a means to yield even richer fragmentation patterns. 44,46 We have explored UVPD at 193 nm for characterization of glycolipids, including lipid A, and found that UV photoexcitation promotes extensive C-C, C-N, C-O, glycosidic and cross-ring cleavages which contribute to the highly informative fragmentation patterns observed upon UVPD.…”
Section: Introductionmentioning
confidence: 99%
“…44,46 We have explored UVPD at 193 nm for characterization of glycolipids, including lipid A, and found that UV photoexcitation promotes extensive C-C, C-N, C-O, glycosidic and cross-ring cleavages which contribute to the highly informative fragmentation patterns observed upon UVPD. 41,6166 UVPD has allowed unusual modifications to be accurately pinpointed and isobaric species to be differentiated. 41,6166 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The radical species generated by PD can be collisionally activated to stimulate migration of the radical that eventually leads to radical directed dissociation (RDD). This method differs from other photoactivation experiments where photons are the primary initiators of the observed fragmentation, as is the case for ultraviolet photodissociation (UVPD) [26][27][28][29] and infrared multi-photon dissociation (IRMPD) [30,31] based experiments.…”
Section: Introductionmentioning
confidence: 99%